2022
DOI: 10.1093/gerona/glac171
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Aortic Calcification, Bone Mineral Density, and Fractures: A Systematic Review and Meta-analysis of Observational Studies

Abstract: Background Abdominal aortic calcification (AAC) has been inconsistently associated with skeletal health. We aimed to investigate the association of AAC with bone mineral density (BMD) and fracture risk by pooling the findings of observational studies. Methods Medline, EMBASE, Web of Science and Google Scholar were searched (August 2021). All clinical studies that assessed the association between AAC and BMD or fracture were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…[11] Overall, falls and fracture risk estimates using ML-AAC24 appear consistent with manually assessed AAC, which aligns with the good levels of agreement reported between the ML-AAC24 and AAC scored by trained imaging specialists. [13] We and others have shown that the presence and extent of manually assessed AAC is associated with impaired musculoskeletal health, [7,8,11] increased risk for all-cause mortality and cardiac events, [6] as well as late-life dementia hospitalizations and deaths. [25] Recently, we reported that women with higher ML-AAC24 had increased risk of all-cause mortality and CVD-related mortality.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…[11] Overall, falls and fracture risk estimates using ML-AAC24 appear consistent with manually assessed AAC, which aligns with the good levels of agreement reported between the ML-AAC24 and AAC scored by trained imaging specialists. [13] We and others have shown that the presence and extent of manually assessed AAC is associated with impaired musculoskeletal health, [7,8,11] increased risk for all-cause mortality and cardiac events, [6] as well as late-life dementia hospitalizations and deaths. [25] Recently, we reported that women with higher ML-AAC24 had increased risk of all-cause mortality and CVD-related mortality.…”
Section: Discussionsupporting
confidence: 78%
“…[11] In support of the current results showing poorer bone health with moderate to extensive ML-AAC24, a meta-analysis of 30 studies showed that those with any/advanced AAC had lower BMD at the total hip, femoral neck, and lumbar spine. [11] Overall, falls and fracture risk estimates using ML-AAC24 appear consistent with manually assessed AAC, which aligns with the good levels of agreement reported between the ML-AAC24 and AAC scored by trained imaging specialists. [13] We and others have shown that the presence and extent of manually assessed AAC is associated with impaired musculoskeletal health, [7,8,11] increased risk for all-cause mortality and cardiac events, [6] as well as late-life dementia hospitalizations and deaths.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations